Love attitudes in undergraduate students’ Romantic relationships - Rocha Narváez, Brenda Liz; Avendaño Parra, Claudia Estella; Barrios Alonso, Miguel Alfredo; Polo Madera, Adalgisa (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This study shows an analysis and identification of the most common types of love in a relationship using the Love Attitude Scale (Hendrick & Hendrick). The scale identifies 6 types of love on the basis of Lee´s typology of love styles (1988). The study was conducted on the sample of 310 students (155 females and 155 males) from different degrees at Pedagogical and Technological University of Colombia in Tunja. Eros, Ludus, Storge, Pragma, Mania and Agape were assessed through frequency analysis, comparative gender, variables of correlation and t-test. Most of the students are identified with Eros, Storge and Agape. Eros and Agape are important for women while for men are Eros and Storge. There is a significant correlation for the same styles. Students’ relationships are characterized by passion, commitment, friendship and emotional intimacy